Differences in clinical characteristics among 726 patients with Chinese herbal medicine- or Western medicine-induced liver injury. Issue 32 (12th August 2022) - Tan, Kangan; Yang, Wanna; Pang, Lili; Hou, Fengqin
Abstract : The differences between Chinese herbal medicine (CHM)- and Western medicine (WM)-induced liver injury have rarely been reported. Our aim was to investigate the clinical features of patients with drug-induced liver injury (DILI) caused by CHM or WM. The medical records of 726 DILI patients were retrospectively collected at Peking University First Hospital from January 1995 through August 2019. The number of inpatients with DILI in our hospital showed an increasing trend over time. The incidence of DILI caused by CHM exhibited a linear trend toward an increase with time ( P = .0012). Of the 726 DILI patients, females accounted for 65.8%. There were 353 cases (48.6%) caused by CHM and 225 cases (40.0%) caused by WM. The 3 most common causative CHMs were Polygonum multiflorum (38 cases), Fructus Psoraleae (35 cases), and Epimedium (26 cases). The proportions of female patients, alanine aminotransferase (ALT) levels, aspartate aminotransferase (AST) levels, total bilirubin (TBIL) levels and antinuclear antibody (ANA) positivity rates among cases caused by CHM were higher than those of cases caused by WM ( P < .05). There were more patients with severe cases caused by CHM than with severe cases caused by WM ( P < .05). The clinical characteristics of DILI caused by CHM differ from those caused by WM. The incidence of DILI caused by CHM is increasing yearly. The medication time of DILI caused by CHM is longer than that of DILI caused by WM, and the severity is greater. Therefore, it is necessary to scientifically and rationally use traditional CHM and monitor liver function. For DILI caused by CHM, the CHM prescription should be recorded in detail to provide detailed clinical data for scientific research on the liver toxicity of CHM.